Engagement to school tasks in primary school students from two educational institutions in Metropolitan Lima, Peru - Veliz-Huanca, Fátima Brenda (2021)
The present research aimed to determine the level of engagement to school tasks in primary school students and the differences between students according to their gender and the grade they study. The study had an observational, descriptive comparative level and cross-sectional design, and had a sample made up of 121 students from 4th to 6th grade of primary school from two educational institutions in Metropolitan Lima, Peru, aged between 9 and 12 years old, in whom Rigo and Donolo’s Scale of Commitment to School Tasks was applied. The results indicate that the high level predominated in the three dimensions of commitment: affective (57.9 %), behavioral (64.5 %), and cognitive (69.4 %). Comparison according to gender and the educational institution did not show significant differences in any dimension. Concerning grade, only found a significant difference for the cognitive dimension (p=0.030). It is concluded that there is a high level of engagement to school tasks among primary school students, this being higher among those who belong to sixth grade, for the cognitive dimension.